1996
DOI: 10.1021/ic951550e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monocarbollide Complexes of Rhodium

Abstract: The compounds [RhX(PPh 3 ) 3 ] react with nido-7-NH 2 Bu t -7-CB 10 H 12 in toluene to give the 16-electron complexes [RhX(PPh 3 )(η 5 -7-NH 2 Bu t -7-CB 10 H 10 )] (1a, X ) Br; 1b, X ) Cl). The structure of the zwitterionic molecule 1a was determined by X-ray crystallography. Crystals are monoclinic, space group P2 1 /c, with a ) 12.937(3) Å, b ) 18.101(4) Å, c ) 14.695(4) Å, β )104.21(2)°, and Z ) 4. The metal atom is coordinated on one side by Br and PPh 3 groups and on the other in the pentahapto manner by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
(24 reference statements)
4
18
0
Order By: Relevance
“…Recently in our laboratories, it was shown that the carbaborane 7-NH 2 Bu t -nido-7-CB 10 H 12 reacts with [RhCl-(PPh 3 ) 3 ] in refluxing toluene to give 16-electron [1-NH 2 Bu t -2-Cl-2-PPh 3 -closo-2,1-RhCB 10 H 10 ]. 9 This contrasts with the earlier work of Hawthorne et al, in which the non-N-substituted carbaborane 7-NH 3 -nido-7-CB 10 H 12 was found to react with the same rhodium reagent in methanolic KOH solution to give the anion [1-NH 2 -2,2-(PPh 3 ) 2 -2-H-closo-2,1-RhCB 10 H 10 ] Ϫ . 10 Significantly, the latter rhodium-carbaborane complex, upon mild thermolysis, forms dimeric [2,2Ј-µ-H-{1,2Ј-µ-NH 2 -2-PPh 3closo-2,1-RhCB 10 H 10 } 2 ] Ϫ , in which each of the µ-NH 2 units forms a bridge between the cage-carbon atom of one {RhCB 10 } cluster and the rhodium centre of the other.…”
Section: Introductionmentioning
confidence: 72%
“…Recently in our laboratories, it was shown that the carbaborane 7-NH 2 Bu t -nido-7-CB 10 H 12 reacts with [RhCl-(PPh 3 ) 3 ] in refluxing toluene to give 16-electron [1-NH 2 Bu t -2-Cl-2-PPh 3 -closo-2,1-RhCB 10 H 10 ]. 9 This contrasts with the earlier work of Hawthorne et al, in which the non-N-substituted carbaborane 7-NH 3 -nido-7-CB 10 H 12 was found to react with the same rhodium reagent in methanolic KOH solution to give the anion [1-NH 2 -2,2-(PPh 3 ) 2 -2-H-closo-2,1-RhCB 10 H 10 ] Ϫ . 10 Significantly, the latter rhodium-carbaborane complex, upon mild thermolysis, forms dimeric [2,2Ј-µ-H-{1,2Ј-µ-NH 2 -2-PPh 3closo-2,1-RhCB 10 H 10 } 2 ] Ϫ , in which each of the µ-NH 2 units forms a bridge between the cage-carbon atom of one {RhCB 10 } cluster and the rhodium centre of the other.…”
Section: Introductionmentioning
confidence: 72%
“…Although much of the group's initial work with 11-vertex monocarborane ligands involved metal-phosphine fragments, [23] it is only very recently that such moieties have been incorporated into complexes with the smaller monocarboranes. Of particular interest were the products obtained by reaction of the [closo-1-CB 8 H 9 ] À anion with fM(PEt 3 ) 2 g nþ cations (M=Rh, n ¼ 1; M=Pt, n ¼ 2).…”
Section: Recent Workmentioning
confidence: 99%
“…Thus the compounds [RhX(PPh 3 ) 3 ] react with 7-NH 2 Bu t -nido-7-CB 10 H 12 in toluene to give the 16-electron zwitterionic Rh III complexes [1-NH 2 Bu t -2-X-2-PPh 3 -closo-2,1-RhCB 10 H 10 ] (3a, X = Cl; 3b, X = Br) [16]. The structure of 3b was confirmed by X-ray diffraction analysis, which showed that the rhodium is coordinated on one side by Br and PPh 3 groups and on the other in the pentahapto manner by the open CBBBB face of the carborane ligand.…”
Section: Rhodium Compoundsmentioning
confidence: 99%
“…In contrast with the reactions of the compounds [RhX(PPh 3 ) 3 ] with 7-NH 2 Bu t -nido-7-CB 10 H 12 that yielded 3a,b, the cobalt reagent [CoCl(PPh 3 ) 3 ] only reacted after prolonged refluxing for several hours in toluene, unexpectedly yielding the 18-electron arenecobalt complex [1-NHBu t -2-(g 6 -C 6 H 5 Me)-closo-2, 1-CoCB 10 H 10 ] (11a) [16]. Formation of 11a prompted an investigation as to whether other structurally similar arene-rhodium compounds could be obtained from the reagent 3a.…”
Section: Rhodium Compoundsmentioning
confidence: 99%